2016
DOI: 10.1080/15384101.2016.1170271
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species-mediated genomic instability in low-dose irradiated human cells through nuclear retention of cyclin D1

Abstract: Mitochondria are associated with various radiation responses, including adaptive responses, mitophagy, the bystander effect, genomic instability, and apoptosis. We recently identified a unique radiation response in the mitochondria of human cells exposed to low-dose long-term fractionated radiation (FR). Such repeated radiation exposure inflicts chronic oxidative stresses on irradiated cells via the continuous release of mitochondrial reactive oxygen species (ROS) and decrease in cellular levels of the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 73 publications
(94 reference statements)
0
38
0
1
Order By: Relevance
“…We recently showed that long-term FR exposure elevates mitochondrial OXPHOS in response to the persistent energy requirement of the DNA damage response (8). The activation of mitochondrial OXPHOS leads to the continuous mitochondrial ROS generation and a decrease in antioxidant GSH levels (35). Alterations in GSH levels are not observed following SR (9).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that long-term FR exposure elevates mitochondrial OXPHOS in response to the persistent energy requirement of the DNA damage response (8). The activation of mitochondrial OXPHOS leads to the continuous mitochondrial ROS generation and a decrease in antioxidant GSH levels (35). Alterations in GSH levels are not observed following SR (9).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting abnormal nuclear retention of cyclin D1 induced genomic instability in long-term FR irradiated cells. [10][11][12] In contrast, NSCs showed the lack of effects on induction of mitochondrial activity by long-term FR. These cells exhibited efficient DNA repair during FR exposure intervals and resistance to long-term FR as evident by no g-H2AX and RAD51 foci.…”
Section: Resistance To Long-term Fr In Nscsmentioning
confidence: 93%
“…9 Thus, mitochondria control both the survival and death of cells after IR. 10 We recently determined that repeated exposure to fractionated radiation (FR) with low doses of X-rays for 31 d (long-term FR) induces chronic oxidative stress in human fibroblasts via the mitochondria-mediated perturbation of reduction/oxidation (redox) control. 11 Elevated levels of mitochondrial ROS disturb cell cycle signaling via protein oxidation and induce genomic instability due to nuclear cyclin D1 retention in long-term low-dose irradiated cells.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive autophagy is induced in neuron due to overexpression of glycogen synthesizing proteins and that the excessive autophagy is the cause of the death of many cellular organelles like mitochondria. Other studies, also suggest that enhanced autophagy may contribute to neuronal death in various pathological conditions including cerebral ischemia (Shi et al, 2012). Still, arguments exist whether increased autophagy activities lead to autophagy neuronal death (Wong and Cuervo, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that after a high dose of IR, cytochrome c is released by mitochondria to induce apoptosis in irradiated cells (Wang, 2001). Therefore, mitochondria control the death and survival of cells after IR (Shimura and Kunugita, 2016).…”
Section: Introductionmentioning
confidence: 99%